Role SOS Children Village Through Family Strengthening Programs in The Development of Children and Adolescents: Study in Gampong Pasie Mesjid Meureubo District, West Aceh Regency - Desi Purnama Sari (Seutia Hukamaa Cendekia, 2024)
Family Strengthening is one of the programs at SOS Children Village that aims to strengthen economically vulnerable families. The author is interested in research by raising the title Role SOS Children Village Through Family Strengthening in Child and Adolescent Development (Study in Gampong Pasie Mesjid, Meureubo District, West Aceh Regency). This research aims to determine the development of children and adolescents carried out by SOS Children Village through Family Strengthening, to find out the obstacles faced by SOS Children Village and to know the strategy of SOS Children Village in dealing with barriers experienced in the development of children and adolescents. This research uses qualitative methods, including interviews, documentation, and observation data collection techniques. The research results from interviews explain that there are two types of development categories carried out by Family Strengthening, namely for PAUD and elementary school children in the form of calistung training and for teenagers in the form of training soft skills in the form of computer technology training, handicraft training, cake and drink processing training as well public speaking. The obstacles faced are a lack of commitment from children and teenagers to participate in the program and differences in the level of absorption of mentors who spend a long time providing understanding to the children. Strategy SOS Children Village deals with obstacles to the development of children and adolescents by motivating children and adolescents who take part in training. The mentor patiently guides children and adolescents who lack absorption capacity during the learning process.